(untitled) (Journal of International Studies, 2013)
Mongolia Politics Democratization: Foreign Factors The article discusses the foreign policy aspects of the democratization of the post-socialist Mongolia. In fact Mongolia is only post-socialist state in the Central Asia region that has achieved success in the democracy transition process. Unique geopolitical position, the strategy of the “third neighbor”, national security and economic interests have largely determined the nature and direction of democracy transition in Mongolia.